Kerion Celsi: A report of two cases due to Microsporum gypseum and Trichophyton tonsurans - Edoardo Torres-Guerrero; Erick Martínez-Herrera; Stefanie Arroyo-Camarena; Carlos Porras; Roberto Arenas (Our Dermatology Online, 2015)
Tinea capitis is a scalp fungal infection involving the hair. Inflammatory cases are usually caused by zoophilic and geophilic species of the genus Microsporum and Trichophyton, and are almost always seen in children. The most effective treatments are with Griseofulvin, itraconazole and terbinafine. We report two cases in children 5 and 7 years old, in which Microsporum gypseum and Trichophyton tonsurans were isolated.